2010
DOI: 10.1152/japplphysiol.00904.2009
|View full text |Cite
|
Sign up to set email alerts
|

Significant blood resistance to nitric oxide transfer in the lung

Abstract: Lung diffusing capacity for nitric oxide (DLNO) is used to measure alveolar membrane conductance (DMNO), but disagreement remains as to whether DMNO=DLNO, and whether blood conductance (thetaNO)=infinity. Our previous in vitro and in vivo studies suggested that thetaNO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…However, it has been estimated that DL NO would not need to be adjusted unless the hemoglobin concentration is Ͻ8 g/dl (50). This is apparent in the data reported by Borland et al (6) and in keeping with previous observation that changes in hemoglobin concentrations like measured in the present study would not be expected to affect DL NO (42).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, it has been estimated that DL NO would not need to be adjusted unless the hemoglobin concentration is Ͻ8 g/dl (50). This is apparent in the data reported by Borland et al (6) and in keeping with previous observation that changes in hemoglobin concentrations like measured in the present study would not be expected to affect DL NO (42).…”
Section: Discussionsupporting
confidence: 89%
“…Most recently, Borland et al (6) reported on membrane oxygenator and experimental animal preparations showing that the replacement of whole blood by hemolyzed blood and cell-free hemoglobin solution actually increased DL NO , with demonstration of a finite value for NO of ϳ4.5 ml NO(ml blood·min·mmHg) Ϫ1 (6). This is similar to that initially reported by Carlsen and Comroe in 1958 (8).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…that y NO is infinity, a view originally asserted by the Bordeaux group. 7 Nitric oxide transfer is now known to increase with hemolysis in vitro 8 and with addition of a cell-free blood substitute in vitro and in vivo 9 indicating that y NO is finite and that DL NO < Dm NO . We and the Bordeaux group 10 recommend using the values for y NO and y CO derived from rate constants measured using the Continuous Flow Rapid Reaction apparatus at the University of Pennsylvania.…”
mentioning
confidence: 99%
“…We have to admit that we were not able to repeat the calculation done by Zavorsky and Borland using the yNO and yCO values they supplied in the table legend (in reality there must be a typo as yNO and yCO were reported in the legend but only yNO ¼ 4.5 ml ml À1 mm Hg À1 min À1 in the table). In this regard the presence of a defined yNO value, 27 albeit a fascinating issue, is still a matter of debate.…”
mentioning
confidence: 99%